ANALYSIS OF THE INFLUENCE OF DEMOCRATIC PARENTING PATTERNS ON CHILDREN'S INTERPERSONAL COMMUNICATION USING SEM-PLS - Sudrimo, Sella Nofriska; Mutmainnah, Annisa (Jurnal Statistika dan Aplikasinya, 2025)
Humans are gregarious and lonely beings who must interact with one another to exchange thoughts, knowledge, or feelings. This can be done through written, oral, nonverbal, or gestural means. Interpersonal communication is the process of direct, in-depth communication between two people or a small group of people through distinctive touch and message exchange. Interpersonal communication is one of the communication skills that should be taught from an early age since effective communication is communication that other people can accept and understand. The process of direct, in-depth conversation between two or a small group of individuals via physical touch and message exchange is known as interpersonal communication. Particularly for kids between the ages of 10 and 12, when they are going through a phase of adjusting to their surroundings, including making friends, effective interpersonal communication is crucial. This study aimed to determine the effect of democratic parenting patterns on interpersonal communication in children aged 10-12 years. The research data were 59 children aged 10-12 years at SD Hidayatullah, Salak Village, Klawasi Village, Sorong City, Southwest Papua. This type of research is quantitative research with the PLS-SEM method. From the data analysis, it was obtained that the valid indicators were X.2, X.9, Y.2, Y.3, and Y.7. The results of the t-statistic value were 3.773, which was greater than the t-table value of 2.003 (3.773 > 2.003). This means that democratic parenting patterns of parents significantly influence interpersonal communication in children aged 10 to 12 years. The analysis results also obtained an f-square value of 0.237, which means that the democratic parenting pattern of parents has quite an effect on children's interpersonal communication.